I believe I can fly… but in polluted air, why? Bird feathers as an example of environmental contaminant monitoring - Świsłowski, Paweł; Hebda, Grzegorz; Zinicovscaia, Inga; Chaligava, Omari; Isinkaralar, Oznur; Isinkaralar, Kaan; Rajfur, Małgorzata (Elsevier BV, 2025)
Metallic element pollution is a global environmental problem, and it is important to study various local conditions to understand the mechanisms on a larger scale. Environmental contamination can be studied in many ways, but non-destructive techniques and methods that preserve the sample are increasingly gaining attention, especially in relation to studies on living organisms. The present study aimed to analyze the feathers of the great tit (Parus major) for Al, S, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Cd, Ba and Hg content. Discriminant analysis showed that according to elemental composition young females and males make separate groups. At the same time, old birds are in the same group. From principal component analysis (PCA), elements distribution depends on age and gender and sources of elements can be natural and anthropogenic. However, not all element accumulation was dependent on both parameters: Al, Cr, Fe, and Ni were statistically significant from both parameters. Bird feathers can be regarded as promising biomonitors of air quality.
Keywords: Male; Avian; Air Pollutants; Metals; Parus major; Air Pollution; Biomonitoring; External pollution; Animals; Female; Feathers; Elements; Environmental Monitoring